Analysis of the site fidelity between male and female humpback whales, visiting the Esmeraldas coasts (Ecuador) - Karla Rojas; Judith Denkinger; Venancio S. Arahana B.; Denisse Dalgo; María de Lourdes Torres P. (ACI Avances en Ciencias e Ingenierías, 2014)
Humpback whales (Megaptera novaeangliae) migrate across the world’s oceans from feeding grounds in polar waters in high latitudes to breeding grounds in tropical waters. Although this species is predictable in its areas of occurrence, there are several poorly understood aspects of its migration patterns. This study aims to evaluate the differences between site fidelity of male and female humpback whales off the coast of Esmeraldas (Ecuador) for the years 2010, 2011 and 2012. A total of 57 whale skin samples were obtained using a biopsy system. For sex determination, primers SFY1204 and SFY0097 were used. A variable section of the mitochondrial DNA control region (D-loop) was amplified by PCR and sequenced to identify haplotypes. Of the humpback whale samples analyzed, it was found that 12 corresponded to females and 44 to males, and a total of 23 different haplotypes were identified. Molecular variance analysis (AMOVA) showed that males had higher site fidelity, although a significant difference was found in the haplotype frequency and nucleotide composition between males within the 2010 and 2011 seasons. These differences were not found within the seasons of 2010-2012 and 2011-2012, which can be attributed to the fact that samples of 2010 were collected in August, when males are in resident groups, while samples of 2011 were collected in July when most males can be in transit to breeding areas further north in Costa Rica and Panama. In addition, females showed no significant differences in haplotype frequency and nucleotide composition, although between female humpback whales of the 2010 and 2012 seasons, only one haplotype was shared. These results may be due to the relatively small number of female samples. These findings may suggest that although male humpback whales disperse in the tropical breeding ground from Southern Ecuador to Northern Costa Rica, they return each year to their native breeding ground. On the other hand, females probably remain in feeding sites during alternate years, to recover from the energy expenditure of gestation and lactation.